Mini knitted toys : over 30 cute and easy knitting patterns - Ishii, Sachiyo (Search Press, 2016)
"Let your inner child out to play! Create simple toys such as animals, cars, trains, fairies and cupcakes, and then try your hand at larger toy sets, including a castle under siege, an alien invasion, a prehistoric play-scene and a fairytale cottage complete with magical characters!,"--page [4] of cover.